2016
DOI: 10.1177/1687814016647947
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of hydraulic excavator working device based on multiple surrogate models

Abstract: The optimal design of hydraulic excavator working device is often characterized by computationally expensive analysis methods such as finite element analysis. Significant difficulties also exist when using a sensitivity-based decomposition approach to such practical engineering problems because explicit mathematical formulas between the objective function and design variables are impossible to formulate. An effective alternative is known as the surrogate model. The purpose of this article is to provide a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…e digging operation using an excavator bucket is a typical and complex soil-bucket interaction process, in which the loads acting on the bucket are uncertain and the stresses in the bucket material are variable due to a constantly changing environment. e traditional deterministic design method takes no account of these uncertainties in loading condition and calculates the design loads under limiting working condition according to the theoretical or empirical load model [1][2][3][4]. us, the highstrength structures are designed at the expense of increased structure weight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…e digging operation using an excavator bucket is a typical and complex soil-bucket interaction process, in which the loads acting on the bucket are uncertain and the stresses in the bucket material are variable due to a constantly changing environment. e traditional deterministic design method takes no account of these uncertainties in loading condition and calculates the design loads under limiting working condition according to the theoretical or empirical load model [1][2][3][4]. us, the highstrength structures are designed at the expense of increased structure weight.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the related research integrating the uncertain resistive force model into the bucket structure optimization design framework has not been reported. On the aspect of structure design, Qiu et al [2] conducted the optimal design of an excavator's working device including the boom, stick, and bucket based on multiple surrogate models. e work of Qiu et al [2] still belongs to the field of ultimate strength design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research works have been conducted and reported on the structural stress analysis and optimization design for the working attachment of an excavator. 1015 Maury et al. 10 carried out failure analysis for the weld-cracked boom of a mining excavator.…”
Section: Introductionmentioning
confidence: 99%
“…To improve computational efficiency, Qiu et al. 15 investigated the applications of multiple surrogate models in optimal design of the working attachment. Rusiński et al.…”
Section: Introductionmentioning
confidence: 99%